Factors Affecting Performance Of Contractors Working On Private Building Constructions In Addis Ababa. - Zerihun, Degu (My University, 2016)
The construction industry often acts as a catalyst to stimulate the growth of a nation's economy. The industry is often referred to as an engine of growth. However, numerous government reports have criticized the industry's poor performance, especially in terms of productivity, quality and quality systems. In order to improve performance, many construction companies implement the ISO 9000 series, an integrated system to ensure consistency and better performance of construction projects. The preliminary data for this research will be collected through a literature review and the use of a questionnaire survey targeted at some contractors, clients and consultants in some building construction projects. Few experts will be interviewed and their opinions will be taken to identify factors which affect contractor performance in building construction projects. The factors for contractor performance are then classified into twelve broad categories (Cost, Time, Quality, Management, Material, Worker, Health and Safety, Client Satisfaction, Environmental, Execution, Design and Documentation, Productivity) depending on their nature and mode of occurrence. An approach is suggested to carry out ranking of these contractor performance factors by Relative importance index technique. It is hoped that the findings of the paper will help the stakeholders to act on critical contractor performance factor and further try to improve performance of their projects. Keywords: Contractor performance, Relative importance index, KPI, Contractor??s Performance Index. The possibility exists for any construction contractor to fail to filfill the contract requirements associated with a facility. Contractor failure occurs when a contractor is unable to perform his/her contractual duties, thus requiring the facility owner to invoke the contract's nonperformance clause. This paper provides aggregate contractor business failure statistics and outlines potential causes for failure. A framework to identify and quantify the associated costs is also introduced. Several case studies are presented to examine the cause and cost of failure and the means by which the facilities were completed. Alternatives available for project completion when contractor failure occurs are discussed. Recommendations to identify and monitor contractors at high risk for failure are outlined as well. This paper provides facility owners with a greater awareness of the possibility of contractor failure, how to quantify costs of contractor failure, and avoidance techniques.
Factors Affecting Performance Of Contractors Working On Private Building Constructions In Addis Ababa.